2011
DOI: 10.1371/journal.pgen.1001314
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Host Specialization in the Vertebrate Gut Symbiont Lactobacillus reuteri

Abstract: Recent research has provided mechanistic insight into the important contributions of the gut microbiota to vertebrate biology, but questions remain about the evolutionary processes that have shaped this symbiosis. In the present study, we showed in experiments with gnotobiotic mice that the evolution of Lactobacillus reuteri with rodents resulted in the emergence of host specialization. To identify genomic events marking adaptations to the murine host, we compared the genome of the rodent isolate L. reuteri 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
301
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 260 publications
(320 citation statements)
references
References 83 publications
15
301
4
Order By: Relevance
“…In this respect, Drosophila appears to parallel mammals, for which no phylogenetic pattern in the composition of the gut microbiota has been found (Ley et al, 2008a;Muegge et al, 2011). Our results differ from the evidence for congruence between host phylogeny and gut microbiota composition obtained, for example, for bacterial community composition in laboratory cultures of jewel wasps Nasonia (Brucker and Bordenstein, 2012), and wild populations of both great apes/humans and termites (Hongoh et al, 2005); and the genotypes of one bacterial species, Lactobacillus reuteri, in studies that included inbred lab mice and rats (Oh et al, 2010;Frese et al, 2011). An important issue for future work is the ecological factors that dictate the variation in the congruence of host-microbiota phylogenies across different animal groups.…”
Section: Discussioncontrasting
confidence: 95%
“…In this respect, Drosophila appears to parallel mammals, for which no phylogenetic pattern in the composition of the gut microbiota has been found (Ley et al, 2008a;Muegge et al, 2011). Our results differ from the evidence for congruence between host phylogeny and gut microbiota composition obtained, for example, for bacterial community composition in laboratory cultures of jewel wasps Nasonia (Brucker and Bordenstein, 2012), and wild populations of both great apes/humans and termites (Hongoh et al, 2005); and the genotypes of one bacterial species, Lactobacillus reuteri, in studies that included inbred lab mice and rats (Oh et al, 2010;Frese et al, 2011). An important issue for future work is the ecological factors that dictate the variation in the congruence of host-microbiota phylogenies across different animal groups.…”
Section: Discussioncontrasting
confidence: 95%
“…of the donor sample is more preserved when transferred to a recipient of the same species. Previous studies have shown that bacterial species (e.g., Lactobacillus reuteri) can have subpopulations with strong host specificity and a gene content reflecting the niche characteristics for the specific hosts (29). This phenomenon might explain why Clostridiales from human feces colonize mice in lower abundance than Clostridiales with mouse origin.…”
Section: Discussionmentioning
confidence: 99%
“…However, in separate epidemiological studies, the presence of L. reuteri in human guts has been associated with obesity [48][49]. Whether this discrepancy reflects the wide genomic variation of L. reuteri strains or differences [50] in hostmicrobial interactions warrants further investigation. A healthprotective role for L. reuteri in host metabolism, as displayed in the present study, offers mutually beneficial gut symbiont-host relationship and co-evolution [51].…”
Section: Cd25mentioning
confidence: 99%